POTENTIAL YIELD ESTIMATION OF POTATO: COMPARISON OF ESTIMATES OF INFOCROP POTATO AND VERSTEEG AND VAN KEULEN METHODS - Rawat, Shashi; Chauhan, R K; Govindakrishnan, P M (Potato Journal, 2013)
Potential yield estimates were obtained through a computer simulation experiment involving five varieties and 4 dates of planting at eleven locations in InfoCrop potato model. These estimates were compared with the estimates from Versteeg and VanKeulen method by calculating the statistical parameters viz., residual mean square error, coefficient of residual mass, model efficiency and critical difference. The result showed that the two estimates were close to each other.